2003
DOI: 10.1034/j.1399-0004.2003.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of marker or complex chromosomal rearrangements present in pre‐ and post‐natal karyotypes utilizing a combination of G‐banding, spectral karyotyping and fluorescence in situ hybridization

Abstract: The significance of complex chromosomal rearrangements presents a diagnostic dilemma. In the past, the use of G-banding coupled with fluorescence in situ hybridization (FISH) has been the standard approach. The recent development of spectral karyotyping (SKY) and multicolor FISH (M-FISH) has resulted in an increased accuracy of identification of marker or other complex chromosomal rearrangements. However, owing to the additional cost and time associated with SKY or M-FISH, and the restricted availability of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…A very rare de novo Y-autosome translocation consisting of chromosomal regions on chromosomes 5 and Y was found in association with a partial duplication of Yq in a male newborn patient with Cri-du-chat syndrome (karyotype 46,XY.ish der(5)t(Y; 5)(q11.2;p15.3)(SKY+,Xq/YqTEL+,5pTEL-)) . Other studies were performed with comparable results Phelan et al, 1998;Peschka et al, 1999;Heng et al, 2003). Surprisingly, a complex chromosomal rearrangement consisting of 16 fragments was reported in a boy with moderate mental retardation and very short stature.…”
Section: Applications Of Chromosome Analysis Using Sky In Clinical Gesupporting
confidence: 60%
“…A very rare de novo Y-autosome translocation consisting of chromosomal regions on chromosomes 5 and Y was found in association with a partial duplication of Yq in a male newborn patient with Cri-du-chat syndrome (karyotype 46,XY.ish der(5)t(Y; 5)(q11.2;p15.3)(SKY+,Xq/YqTEL+,5pTEL-)) . Other studies were performed with comparable results Phelan et al, 1998;Peschka et al, 1999;Heng et al, 2003). Surprisingly, a complex chromosomal rearrangement consisting of 16 fragments was reported in a boy with moderate mental retardation and very short stature.…”
Section: Applications Of Chromosome Analysis Using Sky In Clinical Gesupporting
confidence: 60%
“…Liehr et al (2006) also report a female diagnosed prenatally with a very small marker (5p) and with mental retardation, VSD, facial dysmorphism and other clinical problems ( Table 1 ). Heng et al (2003) reported a case where SKY clarified an extra chromosomal material as being min(5) with no other available data. Kocarek et al (2004) also reported a developmentally abnormal case with 47 chromosomes and an extra sSMC, characterized with FISH as derived from chromosome 5 (abstract in English, article in Czech).…”
Section: Discussionmentioning
confidence: 99%
“…SKY was done on mitotic spreads as described (25,26). Briefly, cytogenetic slides were denatured and hybridized with human painting probes.…”
Section: Introductionmentioning
confidence: 99%